2022
DOI: 10.3390/jcm11226604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Common Intervertebral Disc Discectomies in the Treatment of Lumbar Disc Herniation: A Systematic Review and Meta-Analysis Based on Multiple Data

Abstract: Objective: Due to recent developments and the wide application of percutaneous transforaminal discectomy (PTED), we herein compare it with microendoscopic discectomy (MED) and traditional open surgery (OD) through surgical indicators and postoperative outcomes to evaluate the advantages and disadvantages of minimally invasive surgery PTED. Methods: This systematic review and meta-analysis was conducted in line with PRISMA guidelines (PROSPERO2018: CRD42018094890). We searched four English and two Chinese datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…LDH is one of the most common diseases that cause LBP and LP, and for treatment, surgery should be considered if the patient does not respond to conservative therapy [ 20 ]. With the continuous improvement of surgical techniques and devices, PELD has gradually become one of the most widely used minimally invasive surgeries and can be used to treat various types of LDH at present [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDH is one of the most common diseases that cause LBP and LP, and for treatment, surgery should be considered if the patient does not respond to conservative therapy [ 20 ]. With the continuous improvement of surgical techniques and devices, PELD has gradually become one of the most widely used minimally invasive surgeries and can be used to treat various types of LDH at present [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among minimally invasive procedures, UBE and PELD had demonstrated comparable therapeutic effectiveness to conventional open surgeries in alleviating symptoms and enhancing functional abilities in LDH patients with less trauma and fast recovery [27,28]. But recent evidence indicated that patients underwent PELD may face a high risk of recurrence and revision rates in comparison to those treated with traditional open surgery and microdiscectomy [29]. Notably, the advancement of MISS in recent years had brought about the introduction of UBE with a lower LDH recurrence during follow-up compared to PLED [30].…”
Section: Advantages and Disadvantages Of Ube Compared With Uniportal ...mentioning
confidence: 99%
“…Discectomy involves a small back incision to remove extruded disk material, relieving nerve pressure. While the primary goal of alleviating nerve impingement remains unchanged, newer methods focus on minimising trauma to the muscle and enhancing visualisation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%